2017
DOI: 10.2196/mhealth.7900
|View full text |Cite
|
Sign up to set email alerts
|

User Participation and Engagement With the See Me Smoke-Free mHealth App: Prospective Feasibility Trial

Abstract: BackgroundThe See Me Smoke-Free (SMSF) mobile health (mHealth) app was developed to help women quit smoking by targeting concerns about body weight, body image, and self-efficacy through cognitive behavioral techniques and guided imagery audio files addressing smoking, diet, and physical activity. A feasibility trial found associations between SMSF usage and positive treatment outcomes. This paper reports a detailed exploration of program use among eligible individuals consenting to study participation and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…As hypothesized, EC participants used the app more often (an average of 19.9 sessions vs 7.3 sessions for SC participants), and a greater proportion reported smoking abstinence at follow-up (14.7% of EC participants vs 6.9% of SC participants). This finding is consistent with previous research showing an association between greater program engagement, or adherence, and higher cessation rates [ 39 , 40 ]. The observed quit rate in the EC arm is similar to that observed from physician advice to quit and low-intensity counseling interventions (average 14%-16%) [ 9 ].…”
Section: Discussionsupporting
confidence: 93%
“…As hypothesized, EC participants used the app more often (an average of 19.9 sessions vs 7.3 sessions for SC participants), and a greater proportion reported smoking abstinence at follow-up (14.7% of EC participants vs 6.9% of SC participants). This finding is consistent with previous research showing an association between greater program engagement, or adherence, and higher cessation rates [ 39 , 40 ]. The observed quit rate in the EC arm is similar to that observed from physician advice to quit and low-intensity counseling interventions (average 14%-16%) [ 9 ].…”
Section: Discussionsupporting
confidence: 93%
“…To our knowledge, this is the first trial that objectively measured duration of user engagement with a smoking cessation app. Previous trials have typically reported number of days of app use (ie, logins), 51 which, as shown in our data, can present a limited picture of engagement with digital technology. Our trial showed that an analysis limited to number of days of app use may have concluded that both interventions were equally engaging.…”
Section: Discussionmentioning
confidence: 68%
“…Modifiable factors most relevant to fertility treatment, reproductive health, and pregnancy complications with compelling quantifiable clinical published evidence were women's BMI (a marker of health and lifestyle), diet (nutrition intake), physical activity, smoking cessation, and stress [2,9,[11][12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Lifestyle Factors Relevant To Fertility Carementioning
confidence: 99%